Stakeholder Theory : Konsep Dasar dan Penerapannya dalam Riset Akuntansi Keberlanjutan - Zul Azmi; Audina Yulianty Simamora; Dian Putri Riri Arinji (CV. ITTC INDONESIA, 2026)
This article examines stakeholder theory as a key conceptual framework in the study of management, corporate governance, and sustainability reporting. The authors emphasize that organizations are accountable not only to shareholders but also to various parties affected by their activities, such as employees, customers, suppliers, local communities, regulators, and the environment. This approach shifts from a focus solely on maximizing shareholder value to managing interconnected relationships to achieve sustainable long-term value. The article discusses the development of this theory along two main lines: strengthening its normative and ethical aspects, and expanding its theoretical application in strategic domains such as sustainability, ESG, and organizational accountability. In the context of sustainability reporting and accounting, this theory serves as a foundation for determining the materiality of environmental-social issues and formulating mechanisms for dialogue with stakeholders. Empirical studies indicate that stakeholder pressure drives the adoption of more transparent reporting practices. Furthermore, the article highlights the processual and ontological dimensions, where stakeholder relationships are viewed as dynamic processes involving interaction, negotiation, and the formation of shared norms. The main objectives of applying this theory include explaining organizational legitimacy and accountability, selecting material issues in reporting, linking strategic values ​​to social responsibility, inclusive governance, and integrating normative and operational ones. The article also outlines three main approaches: normative, instrumental, and descriptive, and their application in sustainability research to assess corporate responses to external pressures. Overall, this theory provides a theoretical lens for accounting research to evaluate reporting quality and stakeholder interactions, with recommendations for integrating quantitative and qualitative methods in future studies.